Itu PERAN BIG DATA DALAM PENGAMBILAN KEPUTUSAN MANAJERIAL DI LEMBAGA PENDIDIKAN ISLAM: PENDEKATAN BERBASIS KECERDASAN BUATAN - Adlani, Nazri; Hanifah, Maria; Alfarizi, Salman (Sekolah Tinggi Agama Islam Al-Muntahy, 2024)
The study on the adoption of Big Data and Artificial Intelligence (AI) in Islamic educational institutions offers a detailed exploration of their potential benefits and challenges. The research aims to identify obstacles faced by these institutions in adopting advanced technologies, assess their opportunities for enhancing managerial effectiveness, and evaluate their impact on educational quality and financial transparency. A qualitative-descriptive approach was employed, incorporating interviews with leaders, administrative staff, and teaching personnel from institutions with varying levels of technological integration. This method provided rich insights into the perceptions and experiences of stakeholders, capturing diverse perspectives on the implementation of Big Data and AI. The findings reveal significant advancements in decision-making processes, enabling managers to respond swiftly and effectively to emerging challenges. AI-driven personalized learning enhances student engagement and outcomes, while the integration of Big Data contributes to transparent financial management by optimizing resource allocation. However, several challenges were identified, including inadequate technological infrastructure, a lack of skilled human resources, and concerns about data privacy and security. These obstacles underscore the need for strategic investments in technology, staff training programs, and robust data security measures. The implications of this study suggest a pathway for Islamic educational institutions toward successful digital transformation. Strategic planning that aligns technology adoption with institutional goals, active stakeholder engagement, and continuous evaluation mechanisms are crucial for achieving sustainable integration. By addressing these elements, institutions can harness the potential of Big Data and AI while remaining aligned with Islamic educational values.